Fabrication and characterization of magnesium based surface composites with hybrid reinforcements by friction stir processing: A review. (2021) - Parray, Mohd Rafiq; Khan, Noor Zaman; Maqbool, Annayath
Abstract: Friction stir processing (FSP) is an eco-friendly process which works on the identical principle as friction stir welding (FSW). FSP is a process for reforming the mechanical properties of the materials by using the stirring motion of the rotating tool against the material whose properties need to be enhanced. FSP was initially used for the fabrication and processing of aluminum surface composites. But after several developments, it is now utilized for the fabrication of several surface composites like magnesium alloys, copper alloys, titanium alloys, ferrous and non-ferrous alloys. Keeping in view of increasing demand of magnesium alloys and composites in automobile, aerospace and transportation industries, the current review is aimed to examine the outcome of using hybrid reinforcement for improvement in micro-hardness, mechanical properties and tribological functioning of magnesium-based surface composites (SCs) manufactured through the FSP. Previous literature reveals that the majority of the work on processing of Mg SC's by FSP has been executed by using magnesium alloys of AZ series and few studies are available on ZE and WE series of magnesium alloys. Currently ZE and WE series of magnesium alloy are becoming the material of choice for several applications of automobile and aerospace industries due to their enhanced mechanical properties. This requires more work to be done on processing of ZE and WE series magnesium alloys.